If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5=6-d
We move all terms to the left:
5-(6-d)=0
We add all the numbers together, and all the variables
-(-1d+6)+5=0
We get rid of parentheses
1d-6+5=0
We add all the numbers together, and all the variables
d-1=0
We move all terms containing d to the left, all other terms to the right
d=1
| 16k-57=3k+99 | | 3n+8(2n+4)=-82 | | -47=-5x+3(5x+11) | | 6=3(g+1) | | 3z4,-16=74 | | 3(u-7)=6 | | |-10k|-2=38 | | 64j-81=24j+39 | | 1=-8-7r-5 | | 3(2u+5)=35 | | t+4/2=3 | | m9-7=-8 | | 3(s+13)-4=5 | | 7r+85=49r+1 | | -2x2+56x=0 | | 4x+6=56+9x | | 5=3+p/4 | | 15c=2000 | | 5x-3=1x=-12 | | 3(u-5)=9 | | 2(t-4)=2 | | 8z-11=20z-23 | | 5x-7x+2=4 | | b2-2=0 | | 9y–13=6y+5 | | .−4x2+8x+44=16 | | 20d+67=23d+52 | | C=254,000(0.65)t | | -5+n3=-8 | | 2c+32=24c-78 | | 15x-2=62x-96 | | r2=100 |